Analysis of Potential Work Accidents Using Job Safety Analysis Method (Comparative Study at CV. Gema Mekanika Mandiri and CV. Huda Jaya) - Aa Kartiwa; Muhamad Khaerudin (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2023)
The focus of this study aims to analyze how the potential for work accidents in CV. Gema Mekanika Mandiri and CV. Huda Jaya. The purpose of this study is to determine the potential for work accidents and efforts to control work accidents carried out by companies using job safety analysis in controlling the potential for employee work accidents. This type of research is a comparative research and this research method uses qualitative methods that describe the results of the analysis of potential hazards in a work process using the Job Safety Analysis worksheet. The collection of research data is carried out by making observations, interviews, documentation and filling in the job safety analysis format. While in analyzing data, researchers use the miles and huberman model method, activities in analyzing data start from data collection, data reduction, data presentation, and data conclusion. The informants in this study numbered 5 people on CV. Gema Mekanika Mandiri and 7 people on CV. Huda Jaya. The results showed that the job on CV. Gema Mekanika Mandiri and CV. Huda Jaya is a job that is at high risk of work accidents seen from indicators detailing work steps, identifying hazards, and determining control measures. Then efforts to control potential work accidents carried out on CV. Gema Mechanics Mandiri is by increasing awareness of the importance of wearing PPE on employees, increasing the number of PPE, rejuvenating employee PPE, and supervising the environment around the workshop, then on CV. Huda Jaya is by increasing awareness of the importance of wearing PPE on employees, increasing the number of PPE, rejuvenating employee PPE, ensuring the work given to employees is balanced and carrying out maintenance of electrical installations